2015
DOI: 10.1002/pros.23060
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor‐β signaling induced during prostate cancer cell death and neuroendocrine differentiation is mediated by bone marrow stromal cells

Abstract: TGF-β signaling resulting in activation of SMAD2 in prostate cancer may be an indicator of cellular stress in the presence of toxic paracrine factors released from the bone marrow stroma, ultimately fostering prostate cancer colonization of bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
2
9
1
Order By: Relevance
“…After that, cells were cultured in DMEM/F12 medium (Hyclone Co, USA) containing mineralization induction agents (0.05 g/L vitamin C, 40 ng/mL dexamethasone and 10 mmol/L β-sodium glycerol phosphate) and 10% fetal bovine serum at 37°C with 5% CO 2 . After two weeks of induced culturing, according to our previous study [ 18 ], cells were seeded into a 96-well plate at a density of 1×10 4 cells per well, and then were treated with fluoride at concentrations of 1 mg/L, 4 mg/L and 16 mg/L with or without 10 μmol/L SB431542 as previously described [ 19 ]. Control group was cultured in medium without fluoride and SB431542.…”
Section: Methodsmentioning
confidence: 99%
“…After that, cells were cultured in DMEM/F12 medium (Hyclone Co, USA) containing mineralization induction agents (0.05 g/L vitamin C, 40 ng/mL dexamethasone and 10 mmol/L β-sodium glycerol phosphate) and 10% fetal bovine serum at 37°C with 5% CO 2 . After two weeks of induced culturing, according to our previous study [ 18 ], cells were seeded into a 96-well plate at a density of 1×10 4 cells per well, and then were treated with fluoride at concentrations of 1 mg/L, 4 mg/L and 16 mg/L with or without 10 μmol/L SB431542 as previously described [ 19 ]. Control group was cultured in medium without fluoride and SB431542.…”
Section: Methodsmentioning
confidence: 99%
“…In PCa, bone is one of the preferred sites for metastasis for adenocarcinoma. During bone metastasis, the cross-talk between PCa cells and BMSCs plays a crucial role in cell survival and apoptosis [29,178]. It has been reported that TGF-β secreted from BMSCs induces pronounced apoptosis in the androgen-dependent cells (LNCaP) compared to androgen independent (C4-2) cells.…”
Section: Neuroendocrine Trans-differentiation (Ned)mentioning
confidence: 99%
“…It has been reported that TGF-β secreted from BMSCs induces pronounced apoptosis in the androgen-dependent cells (LNCaP) compared to androgen independent (C4-2) cells. TGF-β signaling in PCa cells leads to NE differentiation [29]. Although primary NEPC rarely metastasize to the bone, in t-NEPC up to 15% of the bone metastasis are NEPC [20].…”
Section: Neuroendocrine Trans-differentiation (Ned)mentioning
confidence: 99%
See 1 more Smart Citation
“…TGF‐β1 is a member of the TGF‐β superfamily. It is a multifunctional cytokine expressed in a variety of tissue cells, especially the liver (Li, Dong, Cao, & Chang, ; Miles et al, ; Wang, Song, Liu, Fang, & Xiao, ; Wincewicz et al, ). TGF‐β1 participates in various pathophysiological processes of mammals extensively and affects cell proliferation, differentiation, migration, apoptosis and other biological activities (Kajdaniuk, Marek, Borgiel‐Marek, & Kos‐Kudla, ).…”
Section: Introductionmentioning
confidence: 99%